Kelayakan puzzle sebagai alat bantu guru dalam upaya pencegahan kekerasan seksual pada siswi SLB-C - Nikita Dwi Mulyaningsih; Mury Ririanty; Erwin Nur Rif’ah (Universitas Ahmad Dahlan, 2020)
Intellectual disabilities were people who have a level of intelligence so low (below normal) that they needed help in carrying out activities. People with intellectual disabilities can strike sexual violence because of the stigma about disabilities are a-sexual creatures, especially intellectual disabilities. Therefore, the community restricted access to health information, especially sexual matters. Besides that, there were several obstacles in conveying health information to people with intellectual disabilities due to the limitations of mental retardation understanding the contents. This is also supported by the lack of media that is used to deliver material to intellectual disabilities people. The purpose of this research is to produce a puzzle that can protect people with intellectual disabilities from sexual violence. Research and development with a qualitative approach. Using interview, document study and observation methods. The research subjects consisted of eleven people consisting of six teachers of SLB-C TPA Jember, one Headmaster of SLB-C TPA Jember, three psychologists of Garwita Institute and one media expert. Data collection tools are interview guides, observation guides, handphones and stationery. The knowledge about sexual violence and puberty of most informants was still lacking. The informants agreed that girls with intellectual disabilities have a problem with their puberty period and sexual violence. The teachers always give education about puberty and how to protect themselves from sexual violence. The informants also agreed that girls with intellectual disabilities need a puzzle that has message education about puberty and sexual violence.